PERAN AKTIF AYAH DALAM POLA ASUH: STRATEGI DOOR TO DOOR UNTUK MENGATASI STUNTING - Tanjung Anitasari Indah Kusumaningrum; Azka Hayyina; Lintang Martha Sari; Aulia Isna Salsabila; Erlina Nafisyasyari; Mahatma Dewi; Husna Ruwaida; Putik Firdiani Kamila; Shafa Maulidya; Salsabilla Nurmadina; Yuyun Novita; Dhea Destiana; Masandra Maydiana Putri; Maftahul Hamida; Novita Ariesta; Henny Puspitosari Utami (Universitas Muhammadiyah Surakarta, 2026)
Stunting remains a significant problem in Indonesia, with 148.1 million children under five affected globally in 2022. Stunting hinders both physical and cognitive development, with primary contributing factors including inadequate nutrition and caregiving practices. This community service activity aimed to increase fathers’ knowledge about caregiving through a door-to-door approach in Desa Makamhaji. The activity was conducted on December 12 and 16, 2024, following three main stages: planning, implementation, and evaluation. The results showed an increase in fathers’ knowledge scores from 71.88 to 93.75. Fathers’ involvement, such as playing with their children, was shown to strengthen emotional bonding and help detect early signs of stunting. This educational program effectively raised fathers’ awareness of their important role, particularly in ensuring proper nutrition, maintaining environmental hygiene, and providing psychosocial stimulation. Similar interventions are recommended to continue addressing knowledge gaps in community-based stunting prevention.